PERSEPSI PETANI MUDA TERHADAP WIRAUSAHA DI SEKTOR PERTANIAN (Kasus pada Petani Muda di Desa Tenjonagara, Kecamatan Cigalontang, Kabupaten Tasikmalaya) - Heru Mukhamad Qudrotulloh; Enok Sumarsih; Hendar Nuryaman; Nurul Risti Mutiarasari; Tito Hardiyanto (Ma'soem University, 2022)
Young generation is a productive workforce who plays an important role in developing agriculture in order to develop Indonesia. This study aims to describe young farmers based on their characteristics and perceptions of entrepreneurship in the agricultural sector, young farmers based on their business background or family livelihood, and analyze the relationship between the characteristics of young farmers and their perceptions of entrepreneurship in the agricultural sector, and the influence of livelihood backgrounds. their families on young farmers' perceptions of entrepreneurship in the agricultural sector. The research method used a survey method with the number of respondents as many as 20 young farmers. The research was conducted in Tenjonagara Village, Cigalontang District, Tasikmalaya Regency. The data used consists of primary data and secondary data. Data were analyzed using Rank Spearman Correlation and Mann Whitney U Test. The results showed that the characteristics of young farmers were in the medium category. Young farmers' perceptions of entrepreneurship in the agricultural sector are included in the sufficient category. The results also show that there is no relationship between characteristics and perceptions of entrepreneurship in the agricultural sector and there is no influence between family livelihood background and perceptions of entrepreneurship in the agricultural sector.